Nghiên cứu khả năng bảo vệ chống ăn mòn của lớp phủ hữu cơ chứa polyme dẫn điện trên nền thép phủ hợp kim nhôm kẽm. - Hiền, Nguyễn Thị Lê; Phương, Nguyễn Thu; Quý, Lê Thu; Trúc, Trịnh Anh (Vietnam Journal of Chemistry, 2012)
In this work, we have studied the duplex coating on carbon steel (steel/Zn-Al/(epoxy+CP)), in which the epoxies used are E828 and X75 and the CP is the conducting polymers of Ppy, Ppy/Fe2O3 and Ppy/Fe3O4, for protection against corrosion of the metal. The results obtained by electrochemical impedance show the galvanic protection effect of Zn-Al alloy and the influence of the epoxy coatings, which delay the penetrability of electrolyte and reduce galvanic dissolution of Zn-Al alloy, so the protective effiency will be improved. Among these conducting polymers, the Ppy without oxides who give the best protection resultal disperses well in both E828 and X75 epoxies to form homogenous coatings.